Development of the computer-aided diagram (CAD) for electrical machine for undergraduate purpose learning - Mohd Syafiq, Mohd Fuad (2008)
This study developed a system analyses the single phase transformer by generates the equivalent circuit and solve the characteristic such as efficiency of the transformer. This project will be used in undergraduate purpose learning and it will be carried out by using graphical user interface (GUI) of Visual Basic (VB) programming language environment. This system can be divided into two sections which are to obtain the equivalent circuit of the transformer and to obtain the efficiency of the transformer. First stage of the program will prompt user to key in the results from transformer test which are the open-circuit test (no-load test) and short circuit test. Program will analyze the data and the equivalent circuit of the transformer will be display as a results. This function returns the referred equivalent circuit for primary and secondary winding. After equivalent circuits are obtained, in second stage of the program, the user is prompted to enter the load specification to obtain the transformer performance characteristic including an efficiency curve from 25 to 125 percent of full-load.